Konsep Masyarakat Ngada-Flores tentang Mata Golo dan Tanggapan Iman Kristiani - Labu, Norbertus; Leo, Waldetrudis; Lina, Paskalis (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The Ngada people of Flores have a very special way of looking at death, which is known as mata golo. Mata golo is any form of unnatural death. For example, being hit by a vehicle, drowning or being killed. This form of death is always perceived by the Ngada as a curse. It is a result of past sins and mistakes. The purpose of this study is to explore the concept of the mata golo and its interpretation from the perspective of Christian faith. This study adopts an interpretive phenomenological qualitative approach. Observation and interviews were used to collect the data. Research sites were in Tude, Tiwuriwu I village, Jerebuu subdistrict and Gisi, Ratogesa village, Golewa subdistrict, Ngada district. The research subjects were family members of mata golo victims, traditional elders and traditional priests (lima mali). The results of the study show that the Ngada people believe that there are three types of death, which are understood differently: gore gote, mata ade and mata golo. Gore gote is a form of death that should be celebrated and given thanks for, for example, longevity. Mata ade is a natural death, for example due to illness and disease. Mata golo is a death that is not good, unnatural and can be devastating for the family left behind. A Christian perspective, which understands death as an event of faith and salvation in Christ, will be brought to bear on this last point. The study will conclude with some special remarks.